Application of a Healthy Lifestyle to Improve the Quality of Life for the Elderly in Kampung Kaiburse - Pulung Riyanto; Carolus Wasa (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
Health is something that is desired by every human being, because healthy everyone can carry out activities smoothly without interruption, can do a job, and / or work optimally. Advances in science and technology as well as socio-economic improvements have an impact on improving the health status and life expectancy of the community, so that the number of elderly people also increases. The increase in the number of elderly people will have an impact on various lives. The main impact of this increase in the elderly is the increasing dependence of the elderly. Many of us find elderly people sent to nursing homes neglected by their families and other problems. Humans sometimes forget how important health is, especially for the elderly. Currently, people ignore the importance of maintaining health, especially physical. The number of activities carried out so that they forget to maintain and maintain a healthy body. On the other hand, there is still a lack of knowledge and understanding of the importance of physical fitness and a healthy lifestyle, especially for the elderly. Therefore we need a program to improve the quality of life of the elderly. The method used is the Initial Condition Survey, Assistance (Theory and Practice) (Training, Socialization of the Application of a Healthy Lifestyle for the Elderly. The result is that the community practices a healthy lifestyle for the elderly so that they have quality. In addition, after this service, it is hoped that the community will be able to maintain and utilize medicinal plants). has been made in the yard of the posyandu for the elderly.